SISTEM INFORMASI AKUNTANSI PENERIMAAN DAN PENGELUARAN KAS BERBASIS WEB PADA PESANTREN PENGHAFAL AL-QUR’AN AL-KAUTSAR - Rostiani, Yeny; Amelia, Sintia; Rustiadi, Rizzky (ISTEK WIDURI, 2025)
The purpose of this research is to design a web-based accounting information system that can be used to record and manage cash inflow and outflow transactions, as a solution to improve efficiency and accuracy in cash management at the Qur’an Memorization Islamic Boarding School Al-Kautsar Karawang (PPAAK), an educational institution focused on Social-Based Education. The research methodology uses the waterfall approach, which consists of the stages of requirements analysis, system design, implementation, and testing. The system is developed using the PHP programming language and a MySQL database, and is equipped with a user-friendly interface. The main features of this system include recording of cash inflow and outflow transactions, user data management, as well as automatic and periodic generation of cash receipt and expenditure summary reports. With this system, the financial reporting process becomes more efficient and can be accessed in real-time by relevant stakeholders.